Pengaruh Model Pembelajaran Problem Based Learning Terhadap Minat Belajar Matematika Siswa Kelas VIII Pondok Pesantren Al-Irsyad TI Bulaan Kamba - Silvi Yarda Rahmi; Haida Fitri; Aniswita Aniswita; Pipit Firmanti (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This research is motivated by the problems in class VIII of Al-Irsyad TI Bulaan Kamba Islamic Boarding School that the learning process is still centered on the teacher, lack of student response to mathematics learning, lack of student courage to ask the teacher, students still think mathematics is difficult and scary, lack of interest in learning mathematics, and students are less enthusiastic when participating in mathematics learning. One alternative learning that can be done to overcome these problems is to apply the Problem Based Learning learning model. This study aims to determine the effect of the Problem Based Learning learning model on the interest in learning mathematics of class VIII students of Al Irsyad TI Bulaan Kamba Islamic Boarding School. The hypothesis in this study is "there is a significant effect of the Problem Based Learning learning model on the interest in learning mathematics of class VIII students of Al Irsyad TI Bulaan Kamba Islamic Boarding School". This type of research is a pre-experiment with a one group pretest-posttest research design, the population in this study were all students of class VIII of Al Irsyad TI Bulaan Kamba Islamic Boarding School, the sampling used was Random Sampling, first a normality test, homogeneity test, and average similarity test were carried out on the population data. The sample in this study was class VIII A as the sample class. The instrument in this study was a questionnaire on students' interest in learning mathematics. The data analysis technique used in this study was the paired sample t test. The results obtained from the paired sample t test were t count = 2.81 and t table = 2.05 and sig = 0.0045 at a real level of α = 0.05. From these results it can be concluded that H0 is rejected and H1 is accepted. So it can be concluded that there is a significant influence of the Problem Based Learning learning model on the interest in learning mathematics of class VIII students of Al Irsyad TI Bulaan Kamba Islamic Boarding School.